THE THOUGHTS OF IMAM IBN H A JAR AL-H A ITAMI IN THE BOOK OF TUHFATUL MUHTAJ AND ITS RELEVANCE TO THE DEVELOPMENT OF THE CONTRACT ON THE SHARI'AH BANK (MURABAHAH, MUDHARABAH, MUSYARAKAH ) - Erwin Azhari; Fahrurrozi Fahrurrozi; Muhamad Yusup (INFOKUM, 2022)
This research aims to determine the thoughts of Imam Ibn Hajar Al-Haitami in the Tuhfatul Muhtaj book and its relevance to the development of contracts in Shari'ah Bank (Murabahah, Mudarabah, Musharakah). This research is qualitative research with the method of analysis of literature review by making the Tuhfatul Muhtaj book a basic source of study in the contract of Murabahah, Mudarabah, and Musharakah. The results obtained in this research are (i) The Murabahah contract during Imam Ibn Hajar Al-Haitami was still in just one term. In contrast, in Syari'ah Bank the Murabahah contract has experienced developments such as the terms Murabahah non-Order and Murabahah to Order. (ii) The Mudarabah contracts during the time of Imam Ibn Hajar Al-Haitami was still in one type, while Mudarabah contracts in Shari'ah Bank has experienced developments such as the terms Mudarabah Mutlaqah, and Mudarabah Muqayyadah,. (iii) The valid Musharakah contract during Imam Ibn Hajar Al-Haitami is Musharakah 'Inan, while Musharakah contracts in Shari'ah Bank has experienced developments so that there are the terms Musharakah Al-Milk and Musharakah Al-'Uqud, the Murabahah, Mudarabah, and Musharakah contracts during Imam Ibn Hajar Al-Haitami differed from those in Shari'ah Bank current regarding its development and progress.